2012
DOI: 10.1167/iovs.12-10148
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Ocriplasmin in Vitreous

Abstract: Ocriplasmin is autolytic in vitreous. Biologic activity extends to several days following injection. The exact duration will vary based on the presence and concentration of serine protease inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…Pharmacological vitreolysis has been studied as an alternative to vitrectomy and has become a promising medical agent because of its ability to induce PVD, for its stable structure, and as a supplement to observation and vitrectomy in managing selected disorders (5)(6)(7)(8)10) . Previous studies have demonstrated that appropriate patient selection is critical for improving outcomes using ocriplasmin (5)(6)(7)(8)10) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacological vitreolysis has been studied as an alternative to vitrectomy and has become a promising medical agent because of its ability to induce PVD, for its stable structure, and as a supplement to observation and vitrectomy in managing selected disorders (5)(6)(7)(8)10) . Previous studies have demonstrated that appropriate patient selection is critical for improving outcomes using ocriplasmin (5)(6)(7)(8)10) .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that appropriate patient selection is critical for improving outcomes using ocriplasmin (5)(6)(7)(8)10) . The overall frequency of successful release (4 eyes, 57.1%) was higher in this study than in phase III clinical trials (26.5%).…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Its biological activity within the vitreous cavity can be observed no longer than several days post-injection. 31 The drug is available in solution for injection. It is designed for intravitreal use under aseptic controlled conditions.…”
Section: Pharmacological Treatment Of Symptomatic Vmamentioning
confidence: 99%
“…It then enters the endogenous protein catabolism pathway, limiting its biological duration of activity to several days after injection which varies based on the presence and concentration of serine protease inhibitors [17].…”
Section: Pharmacokinetics and Metabolismmentioning
confidence: 99%